Enhancing Lifelong Learning Motivation Among Experienced Educators: A Qualitative Analysis of Bootcamp-style Professional Development (Asean Journal of Engineering Education, 2025)
This study examines the impact of professional development bootcamps—GENACITY, TENACITY, and TENSITY—on the lifelong learning motivation of experienced educators. The research utilizes a qualitative approach, collecting data through pre-bootcamp open-ended questionnaires, post-bootcamp focus group discussions (FGDs), and participant reflections. Framed within Kirkpatrick’s Four-Level Training Evaluation Model and Constructivist Learning Theory, the findings reveal that the bootcamps fostered positive emotional engagement, practical skill acquisition, and behavioral change. Participants expressed increased motivation to implement new teaching strategies, such as active learning, problem-based learning (PBL), and cooperative learning, with many integrating tools like Canva and AI into their practices. However, participants also identified challenges, including time constraints and workload pressures, in sustaining the new strategies. The results indicate that immersive, collaborative professional development programs can reignite educators' passion for continuous learning and offer practical solutions for modern teaching environments. This study emphasizes the importance of reflective practices and follow-up support to ensure sustained impact and proposes that future initiatives prioritize experiential learning and peer collaboration. These findings contribute to the discourse on effective professional development and highlight the potential of bootcamps to address the evolving demands of lifelong learning. The study's limitations include its small, institution-specific sample, which limits generalizability. Future research should involve multiple institutions and larger samples, alongside longitudinal follow-up to validate sustained behavioral change.
Keywords: Lifelong Learning; Professional Development; Educator Motivation; Bootcamp Training; Constructivist Theory